The problem of national values or transformation of values in contemporary culture (Journal of Philosophy Culture and Political Science, 2018)
This article considers the problem of the spreading of the process of globalization, which was refl ectednot only in the political and economic spheres of human life, but also directly touched the spiritual world ofmodern man. Political and economic achievements of the most developed countries hasn’t any infl uence, buttheir lifestyle is becoming a role model. The effect of other cultural samples on the mass consciousness canlead to be transformed by national moral values. The authors comprehensively considering this issue, offer theirconcluding ideas: no by denial of globalization, and the defi nition of its negative infl uence; not by negation of allthe Western samples (Westernization), but by keeping the originality (identity) to establish a dialogue with theWestern culture; identifying infl uence ways of the media on the formation of mass consciousness, to direct theiractivity on revival of a national idea.Key words: value, mass consciousness, national self-identity, globalization, national spirit, national idea.